Neurosarcoidosis: Pathophysiology, Diagnosis, and Treatment. Issue 6 (4th November 2021) - Bradshaw, Michael J.; Pawate, Siddharama; Koth, Laura L.; Cho, Tracey A.; Gelfand, Jeffrey M.
Abstract : Although often regarded as a protean illness with myriad clinical and imaging manifestations, neurosarcoidosis typically presents as recognizable syndromes that can be approached in a rational, systematic fashion. Understanding of neurosarcoidosis has progressed significantly in recent years, including updated diagnostic criteria and advances in treatment. The diagnosis of neurosarcoidosis is established by the clinical syndrome, imaging and histopathological findings, and exclusion of other causes. Mounting evidence supports the use of tumor necrosis factor inhibitors as an important addition to the therapeutic armamentarium, along with glucocorticoids and steroid-sparing cytotoxic immunosuppressants. In this narrative review, we summarize recent advances in the diagnosis and treatment of neurosarcoidosis.